A SEM-PLS Approach: Teacher 4.0 – Are You Competent Enough? - Melor Masdoki (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
Teacher 4.0 is a concept of future educators created to explain the characteristics of educators who can handle various technologies with effective teaching in parallel with the transformation of Education 4.0. Readiness and acceptance of the use of various smart technologies, better known as Technology 4.0 experienced a large-scale shift in the national education system, especially in teaching and learning methods. This includes all levels from primer to higher education institutions. The transformation of 4.0 requires improvement in teachers' competency to enhance teaching and to ensure it is in line with the country’s objective in producing highly competitive, innovative educators and students in the era of 4.0. The need for a measurement tool is important due to the lack of research conducted to test the competence of Teacher 4.0. Thus, this study was conducted to measure the competence of Teacher 4.0 by creating a new instrument adapted from the DigCompEdu model. Appropriate constructs were validated and hypotheses were tested using PLS-SEM approach to evaluate the contribution of each construct towards Teacher 4.0 competency. The sample used in this study involves 274 among MARA teachers’ pre-university institutions across Malaysia. A total of three formative constructs were identified, namely teaching and learning, assessment and facilitating students' Technology 4.0 competence. Questionnaires were distributed to respondents using purposive sampling and the data obtained was analyzed using SEM-PLS software. The results of the analysis show that all constructs have passed sufficient convergent validity. Hypothesis verification analysis shows that all constructs have a positive contribution towards Teacher 4.0 competency. Overall, this study has created a new measurement instrument that can measure the competence of Teacher 4.0 and improvised the DigCompEdu model. Findings can be a reflection indicator for teachers to improve teaching methods and strategies in addition to developing existing competencies. The problems arising from this study can be indicators for educational institutions to ensure that the facilities and infrastructure required for Technology 4.0 can be expanded in line with their needs as an educational support tool.